KELUARGA SAKINAH PERSPEKTIF HADIS (Kajian Hadis Maudhu’í) - tita rosalina (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The family is also the soul and backbone of a country, the physical and spiritual well-being experienced is a reflection of the situation of the family living in the midst of the community itself. Thus, if we want to create baldatun thayyibatun (a good state), the foundation that we must build is a marhamah society, namely the creation of a sakinah family. The pillars that must be upheld to make it happen are faith, mawaddah and mercy. With the figure of a father who is wise, compassionate, gentle and able to educate and raise children with love will shape the child's character to be strong, thus the family is the most important school through a mother's upbringing. This research was made based on a review of several sources of literature review (literature study) or library research that is relevant to the topic discussed, namely the focus on the study of the Sakinah Family including: the understanding or concept of the sakinah family, the characteristics or characteristics of the sakinah family and hadiths hadith about the sakinah family. A sakinah family is a family that is harmonious, happy both physically and mentally, living a calm, peaceful, peaceful life and full of love. The term